Analisis Keanekaragaman dan kelimpahan kupu-kupu (ordo Rhopalocera) berdasarkan kondisi lingkungan - Umu Zulfatu Rizki; Lianah Lianah; Saifullah Hidayat (Biota, 2022)
Mount Muria has abundant natural resources, both flora and fauna, one of which is butterflies. Butterflies as natural pollinators have an important role in the ecosystem. The deterioration of air quality has a negative impact on butterflies because they are quite sensitive to poor air quality and poor lighting. This study aims to analyze the relationship between environmental conditions and butterflies in the Muria Kudus area, carried out in March and June 2020. Butterfly observations were carried out using the quadratic sample transect method with 3 observation stations and measured environmental factors, among others: temperature, humidity, light intensity, altitude and Pb concentration analysis with AAS. The results of the study found 40 species of butterflies consisting of 6 families, with a moderate diversity index, almost merit index and low dominance. Muria area still has good environmental conditions for butterfly breeding. Relative abundance is negatively correlated with light intensity (rcount = -0,855, rtable = 0,811). Averageness is negatively correlated with heigh (rcount=-0,836, rtable=-0,881). The butterfly species Ypthima nigricans, Orsotriaena medus, and Melanitis leda is a specialist butterfly species and the butterfly species Papilio memnon, Leptosia nina, Chersonesia rahria, Mycalesis horsifieldii, and Yphtima horsifieldii is a generalist species butterfly